PROGRAM ENGLISH FOR KIDS: PELATIHAN PERCAKAPAN BAHASA INGGRIS BAGI ANAK USIA SD DI YAYASAN PANTI ASUHAN PENUH PENGHARAPAN MEDAN - Pioro Benevolent Lariest; Bertova Simanihuruk; Anselmus C. A. Bangun; Rosa Maria Simamora; Bonar Gurning (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2026)
This community service program aimed to improve the English speaking skills of elementary school children at Yayasan Panti Asuhan Penuh Pengharapan Medan. The program, titled "English for Kids," was conducted on March 15-16, 2026, and involved 12 elementary school children (grades 1-6) residing in the orphanage. The training employed interactive and enjoyable methods, including ice breaking, flashcards, storytelling, language games, role-play, and short presentations. The activity was carried out over two days with a duration of 3 hours per day. The results showed a significant improvement in the participants' English speaking abilities, marked by increased vocabulary mastery (from only a few words to 15-20 new words), the ability to construct simple self-introduction sentences, and enhanced motivation and self-confidence in communicating in English. All participants successfully performed short self-introduction presentations in front of the class at the end of the program. This activity demonstrated that interactive and enjoyable methods are effective in improving the English speaking skills of orphanage children, while also providing proper educational access for those who have been limited by financial and facility constraints. This program is expected to serve as a model for English learning assistance in other orphanages across Indonesia, particularly in anticipating the Merdeka Curriculum policy that mandates English as a compulsory subject starting in the 2027/2028 academic year.